State as a Firm - "Auster,Richard.D" (London, 1979)
The central element of a formal political structure is the state the authors of this book maintain that states are simply firms, although admittedly ones that procure primarily public goods. "Firm" is the economist's word for the micro decision unit for production. From the perspective on society that all exchanges are subject to the same underlying laws, states are simply service firms. they make decisions regarding certain services used by society: police protection, protection against foreign invasion, sanitation, etc.
Keywords: ".State, The - Economics aspects."